ANALISIS AUDIT OPERASIONAL DALAM MENINGKATKAN EFEKTIFITAS BIAYA OPERASI PADA PT. PLN WILAYAH SULSELBAR - Muhaimin Muhaimin; Amran Amran; Desi Kumala Sari (Universitas Muhammadiyah Makassar, 2019)
Research aims to determine the role of operational audits can increase the effectiveness of operation cost control in Makassar city. The research method used is a qualitative descriptive analysis research method. The data collection techniques used are Library Research and field research that is by conducting interviews to operational audits. The results of research using qualitative descriptive analysis suggest that the operational audit has a role in increasing the effectiveness of operating cost control. Based on the results of research and discussion that has been done can be concluded as follows: (1) Implementation of operational audit in PT PLN (Persero) Sulselrabar region always maintains its identification where operational auditors are given The freedom to complete its responsibilities honestly and to carry out its ability to audit.